Improved enzymatic activity by oriented immobilization on graphene oxide with tunable surface heterogeneity. (1st July 2021) - Zhou, Wenfeng; Rao, Yuan; Zhuang, Wei; Ge, Lei; Lin, Rijia; Tang, Ting; Wu, Jinglan; Li, Ming; Yang, Pengpeng; Zhu, Chenjie; Wang, Hao; Ying, Hanjie
Abstract: The precision design of surface properties of supports and immobilization methodologies is essential for improving the biocatalytic activity of immobilized enzymes. In this study, we proposed a surface heterogeneity regulation strategy of graphene oxide (GO) to oriented immobilize adenylate cyclase (AC). The grafted flexible chain of polyethylene glycol amine (PEG-NH2 ) and maleic anhydride (MAH) on GO surface can adjust the interaction between support and AC. The achieved immobilized AC can eliminate the non-specific adsorption and introduce cushioning effect for the AC's catalytic reaction under extreme conditions. Therefore, the active center of the enzyme can be retained. The introduction of PEG-NH2 improves the activity recovery with 113%. Compared to GO-Ni 2+ @ AC, 8 arm-PEG-NH2 modified GO immobilized AC has 117 times higher catalytic activity. The method proposed in this study provides a possibility to address the issues in enzyme application, such as the purification of enzyme, low enzyme activity caused by cross-linking, and non-specific adsorption due to molecular force on the surface of the supports. The strategy should provide deeper understanding of the oriented immobilization and support modification for improving the activity and stability of the immobilized enzyme. Graphical abstract: Image 1